COVID-19와 IT 서비스: 변화와 대응 - 이정우; 강주영; 이상곤 (한국IT서비스학회지, 2021)
Since the first confirmed case in January 2020, Coronavirus disease 2019(COVID-19) has brought many changes to our society, and Korea is no exception. Some changes are direct and immediate such as restrictions on overseas travel and social distancing, but the others are indirect and slowly adapted such as lifestyle changes impacting industries and businesses. IT service sector is tremendously influenced by COVID-19. IT service is used extensively in response to COVID-19 taking advantage of its non-face-to-face characteristics. In that sense, the industry is positively affected and in some sense invigorated, giving birth to new kind of services. This special issue focuses on introducing how the IT services are affected, what kind of transformations are undergoing, and how these are expedited after COVID-19. This special issue expands and extends the case research section by collecting new IT service case studies concerning these topics. After competitive review process, 11 studies are selected for this special issue which deals with four different but closely related aspects: (1) evolutions of private IT services, (2) transformations in public IT services, (3) impacts in the hospitality and tourism industry, and (4) changes of people’s behavior along with COVID-19. The first set reports on the evolution of private IT services that have created terms such as foodtech and edutech as we enter a rapid non-face-to-face situation. The second set consists of studies dealing with the evolution of public IT services. Evolution and rapid response to non-face-to-face appear to be no exception in the public sector. The third includes studies of hospitality and tourism which is most strongly affected by COVID-19. The last set deals with the behavioral changes of users such as technostress in telecommuting. Lessons learned through best practices and key problems identified in these studies may help us to actively respond to the coming waves of changes incurred by COVID-19 in our society as well as in the IT service industry.
Keywords: COVID-19; Post Pandemic; IT Service; AI; Public Service; Travel Service